SUPERVISI ASIMETRIS HAKIM DALAM KEKUASAAN YUDIKATIF INDONESIA (PERSPEKTIF HUKUM KELEMBAGAAN NEGARA) - Dwi Wahyudi (2021)
Supervision of judges is important to ensure the functioning of the judiciary runs well and efficiently. Each judge essentially has the same portion of supervision. However in practice currently, supervision of the constitutional judges is only carried out internally by the Ethics Council of the Constitutional Judges and by the Honorary Council of the Constitutional Court as the advanced element, while the supervision of other judges is carried out in layers, it is carried out by Supreme Court (as internal supervision) and the Judicial Commission (as external supervision). The asymmetrical pattern of supervision between the constitutional judges and other judges constitutes a legal situation which is being spotlight. The presence of the pragmatic paradigm of society that the status of the Constitutional Court is higher than the Supreme Court is a residue that arises from the implementation of this asymmetric supervision. For this reason, this research is presented as an assessment effort to explore the phenomenon of asymmetric supervision of judges from the perspective of state institutional law. Researchers in this paper chose the type of normative juridical research, which was then combined with three approaches, those were the statute approach, the conceptual approach, and the historical approach. From the results of this research, it was found that the implementation of asymmetric supervision of judges was not based on differences in status between constitutional judges and other judges, but it was present due to legal conditions and complex legal considerations, so that the supervision of all judges could not beeen carried out uniformly yet. It was also found that the Supreme Court institutionally has an equivalent position as the Constitutional Court, the only thing that distinguishes the two is the judicial competence.